IDENTIFICATION OF PREDATORY BIRDS OF PALAWIJA INSECT PEST IN GUNONG PULO VILLAGE OF NORTH KLUET SUBDISTRICT SOUTH ACEH REGENCY - Afrija, Lia Nur; Abdullah, Abdullah; Syafrianti, Devi; Khairil, Khairil; D., Asiah M. (Biofaal Journal, 2023)
Pest control can biodepress the development of insect pests of palawija plants, one of which is by utilizing the potential of predatory birds. Today farmers use synthetic chemical pesticides in insect pest control. This research aims to identify a type of predatory bird that has the potential to control the pest of palawija insects in the agricultural area of Gunong Pulo Village, North Kluet Subdistrict, North Kluet Subdistrict. Data collection was conducted in May 2021 using purposive sampling methods, with transect line observations and quantitative approaches. The results of the study were obtained by bird species that became predators of insect pests, namely Kirik-kirik Biru, Kadalan Selaya, Bubut Alang-alang, Kapasan Kemiri, Layang-layang Api, Pelatuk Merah, Pelatuk Bawang, Apung Sawah, Tiong Lampu Biasa, Bangau Tongtong, Tiong Emas, Bambangan Merah, Cangak Merah, Kuntul Kerbau, Kuntul Besar, Cica Daun Kecil, Cipoh Kacat, Elang Ular Bido, Elang Bondol, Elang Hitam, Kutilang, Merbah Cerucuk, Cabai Merah, Bondol Haji, Perkutut, Punai, Punai Gading, Punai Ungu, and Tekukur. From the results of the study can be concluded there are 30 species of prodator birds from 18 families in Gunong Pulo Village, North Kluet District, South Aceh Regency.